2022
DOI: 10.1007/s40670-022-01581-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of In-person Lecture Attendance in Medical School

Abstract: Introduction Attendance at in-person lectures in medical schools is declining with nearly 28.8% of all active, second-year medical students who reported "almost never" attending in-person lectures during their preclinical years. The objective of this study was to explore the relationship between medical student attendance and performance and investigate students' goal orientation as factors influencing their decision to attend. Methods Participants completed a survey at the end of their second year that asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Teachers and leads across all subjects report a very low attendance rate at small group and larger group teaching and whole cohort lectures and a similar phenomenon has been reported across other medical schools in the UK. Although the literature is still limited on this development, this appears to be a worldwide observation 1. At our institution and within the literature, this change in the attendance was noted to occur prior to the pandemic,2 but became significantly more noticeable following the return to in-person teaching postpandemic.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Teachers and leads across all subjects report a very low attendance rate at small group and larger group teaching and whole cohort lectures and a similar phenomenon has been reported across other medical schools in the UK. Although the literature is still limited on this development, this appears to be a worldwide observation 1. At our institution and within the literature, this change in the attendance was noted to occur prior to the pandemic,2 but became significantly more noticeable following the return to in-person teaching postpandemic.…”
Section: Introductionsupporting
confidence: 50%
“…Although the literature is still limited on this development, this appears to be a worldwide observation. 1 At our institution and within the literature, this change in the attendance was noted to occur prior to the pandemic, 2 but became significantly more noticeable following the return to in-person teaching postpandemic.…”
Section: Introductionmentioning
confidence: 55%
“…2 Moreover, an increasing number of learners seek digital alternatives or complements to in-person didactic lectures. While in-person lecture attendance in medical schools has dwindled over the years, further exacerbated by the COVID-19 pandemic, 3 virtual learning has been increasingly provided as a convenient option for medical education. The new generation of medical students and trainees value accessing learning materials with increased flexibility.…”
Section: The Importance Of Videos In Anesthesia Educationmentioning
confidence: 99%
“…41 Another study also showed that following the COVID-19 pandemic, there has been an increase in the use of virtual learning. 42 Many medical students contend that in-person lecture attendance promotes balancing their social relationships with keeping up with coursework, and it is less critical than virtual learning for preparing for basic science examinations. 42 Understandably, widespread acceptance and use of educational technology will depend on whether or not the product is accessible, widely available, useful, usable, convenient to use, and affordable.…”
Section: Digital Learningmentioning
confidence: 99%
“…42 Many medical students contend that in-person lecture attendance promotes balancing their social relationships with keeping up with coursework, and it is less critical than virtual learning for preparing for basic science examinations. 42 Understandably, widespread acceptance and use of educational technology will depend on whether or not the product is accessible, widely available, useful, usable, convenient to use, and affordable. 34 However, the major barriers to using digital technologies may include limited interactive content, cost constraints, lack of portability, lack of space and quiet environment for those living in crowded conditions, insufficient access to data, and poor internet connectivity.…”
Section: Digital Learningmentioning
confidence: 99%